2015
DOI: 10.1021/ac504684n
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Single Bladder Cancer Cells Using Principal Component Analysis of Time-of-Flight Secondary Ion Mass Spectrometry

Abstract: Time-of-flight-secondary ion mass spectrometry (TOF-SIMS) mass spectra measurements combined with an appropriate sample preparation protocol are the powerful tools to obtain unique information about the chemical composition of biological materials. In our studies, two questions were addressed, i.e., whether it is possible to develop a fixative-based sample preparation protocol and whether it allows one to distinguish between cells originating from various stages of cancer progression. Therefore, four human bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…PCA has been applied for processing the ToF-SIMS data in the research of many fields, such as materials, biology, and medicine. [26][27][28][29][30][31][32] In this study, we collected atmospheric aerosols on different air quality level days of each season in 2015 in an urban area of Beijing and analyzed these aerosols by ToF-SIMS. Since winter is the season with most frequent haze, we compared the mass spectral aerosol data acquired on various pollution level days in winter and analyzed by PCA.…”
Section: Funding Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…PCA has been applied for processing the ToF-SIMS data in the research of many fields, such as materials, biology, and medicine. [26][27][28][29][30][31][32] In this study, we collected atmospheric aerosols on different air quality level days of each season in 2015 in an urban area of Beijing and analyzed these aerosols by ToF-SIMS. Since winter is the season with most frequent haze, we compared the mass spectral aerosol data acquired on various pollution level days in winter and analyzed by PCA.…”
Section: Funding Informationmentioning
confidence: 99%
“…Using PCA, the most useful and significant information can be effectively extracted. PCA has been applied for processing the ToF‐SIMS data in the research of many fields, such as materials, biology, and medicine …”
Section: Introductionmentioning
confidence: 99%
“…The recorded data show changes on the surface of single WM115 cell. The use of the proposed sample preparation protocol enables to record mass spectra (ToF SIMS) on single cells [1] , [2] ( Fig. 1.1 , Fig.…”
Section: Datamentioning
confidence: 99%
“…The AFM images presented below, show surface changes of single WM266-4 cells acquired after each step of the ToF SIMS specialized sample preparation protocol. The presented protocol enables to record mass spectra (ToF SIMS) on single cells [1] , [2] ( Fig. 2.1 , Fig.…”
Section: Datamentioning
confidence: 99%
“…Ide et al showed that changes in lipid composition on breast cancer cell lines can be studied using TOF-SIMS [49]. Gostek et al showed that single bladder cancer cells can be distinguished using TOF-SIMS data and principal component analysis [50]. A recent 3D-MSI-TOF-SIMS study by Passarelli et al using dual beam analysis and depth profiling described drug and metabolite uptake at the single cell level [51].…”
Section: Introductionmentioning
confidence: 99%